Morphological evaluation of cardoon (Cynara cardunculus L.): assessing biodiversity for applications based on tradition, innovation and sustainability - Barracosa, Paulo (2018)
Selected cardoon cultivars established in the “Serra da Estrela” region were analysed to evaluate morphological characteristics related principally to the production of cardoon flowers, which are a compulsory ingredient for particular Mediterranean PDO cheese regions. The biodiversity of twelve cardoon cultivars installed in an experimental field were evaluated over three growing seasons using thirty-four morphological descriptors. Statistically significant differences were found between cultivars for twenty-four morphological characteristics which indicate a wide genetic diversity. The relationship among the cultivars and characteristics was analysed using principal component analysis. A three dimensional template was found to be very significant and explained 71% of the total variation. The first component is dominated positively by plant height, diameter of stalk, inflorescence characteristics and flower production, while the second component is positively dominated by leaf characteristics. Cultivars A26, D32 and D33, present a plant architecture simultaneously well adapted for flower production, ease of harvesting and plant biomass. These characterizations and understandings can be useful for a plant breeding programme to develop cultivars for innovative potential applications besides flowers, and also for application by other cheese producers in Mediterranean regions.